The consumption of walnuts has an impact on decreasing fasting blood glucose levels in individuals with concurrent hyperglycemia and hyperlipidemia: a randomized control trial - Ibu Sukmawati; Sira Sirajuddin; Suriani Rauf (PAGEPress Publications, 2024)
Nationally, the prevalence of Diabetes Mellitus (DM) has increased by 0.5%. In 2013, it was approximately 1.5%, rising to 2.0% in 2018. On the other hand, it is known that administering walnut extract can reduce blood sugar levels in diabetic patients. The aim of this study is to determine the effect of walnut consumption on blood sugar levels. The research was conducted experimentally, using a pre-post test control group design. The research sample consisted of mothers with fasting blood sugar levels ≥200 mg/dL and total cholesterol levels ≥200 mg/dL (hyperglycemic and hyperlipidemic). The total sample size was 50 mothers, divided into 2 groups. Samples were selected using simple random sampling. The intervention involved giving 50 grams of walnut (Canarium Indicum L.) daily for 8 weeks to the treatment group. The research was conducted in the working area of the Paccerakang Community Health Center in Makassar City, Indonesia. Statistical analysis was performed using paired T-tests. There was a decrease in fasting blood glucose levels in the treatment group from 244.12 mg/dL to 195.52 mg/dL. In the control group, there was a slight decrease in blood sugar levels from 236.92 mg/dL to 229.96 mg/dL. Paired T-test analysis in the treatment group showed a value of p=0.00, indicating a significant difference in cholesterol levels before and after the intervention in the treatment group. In the control group, the value was p=0.07, indicating no significant difference in cholesterol levels in the control group. Administering 50 grams of walnuts per day for 8 weeks significantly lowered fasting blood sugar levels in hyperlipidemic and hyperglycemic mothers.